Dupilumab in Elderly Patients With Severe Atopic Dermatitis. Issue 1 (October 2021) - Russo, Filomena; Milanesi, Nicola; Cartocci, Alessandra; Bruzziches, Francesco; Tronconi, Greta; Lazzeri, Laura; D'erme, Angelo Massimiliano; Bagnoni, Giovanni; Gola, Massimo; Cinotti, Elisa; Rubegni, Pietro; Flori, Maria Laura
Abstract : Background: Atopic dermatitis (AD) in the elderly has been poorly investigated, although its incidence is gradually increasing mainly in industrialized countries. Age-specific factors in older patients must be considered when selecting treatment options. Objectives: To evaluate the efficacy and tolerability of dupilumab in treating elderly patients with severe AD. Methods: This was a retrospective, multicenter study involving 26 elderly patients (age, ≥65 years) with severe AD who were treated with dupilumab for at least 16 weeks. Absolute and percentage frequencies were used to evaluate qualitative variables and mean and SD for quantitative ones. For Eczema Area and Severity Index (EASI), Pruritus Numeric Rating Scale (NRS), and Dermatology Life Quality Index (DLQI), the median was also calculated. Wilcoxon test was used to evaluate the variations in EASI, Pruritus NRS, and DLQI observed between the 2 examinations. Results: After 4 months of therapy, the majority of patients showed a significant improvement in EASI (64.4%), Pruritus NRS (58.2%), and DLQI (44.9%). Only 11% of patients reported mild or moderate conjunctivitis. Conclusions: To the best of our knowledge, this is the first study concerning the use of dupilumab in the elderly with severe AD. Our data show the effectiveness of dupilumab in this particular population with a lower percentage of conjunctivitis than observed in studies on adults and also excellent control of itching. Only larger, controlled case studies will be able to clarify whether the dosage or frequency of administration of dupilumab in these patients should be different from the protocol used for adults.